Review of the Tribological Characteristics of Synovial Fluid. (2016) - Prekasan, D.; Saju, K.K.
Abstract: Movement of the knee joint requires an effective lubrication mechanism. Synovial fluid is reported to serve this function. Synovial fluid is an extra cellular biofluid present in the synovial joint of living beings. Numerous studies have been conducted on the characteristics of synovial fluid. Total Knee Replacement is seen as a permanent cure to acute arthritic condition. Synovial fluid supplementation is seen to enhance the life of Total Knee Replacement Joints. Development of an effective synovial fluid for this purpose is being researched worldwide. This paper reviews the properties of synovial fluid as reported under various studies and can form the basis for development of a good artificial synovial fluid.